Significance of religion in the socioeconomic success of Nattukottai Chettiars in lower Burma, 1900-1930 - Lim, Clara Yan Fang (2017)
The presence of Nattukottai Chettiars in Southeast Asia during the British colonial period was not uncommon due to the presence of great business opportunities. While much literature has been written on the Chettiar community, there is little emphasis on the sociocultural aspect of the community, especially how their religion had influenced their commercial and daily life. This paper is concerned, in particular, about the role of religion in helping the community achieve socioeconomic success in the Lower Delta region of colonial Burma from 1900 to 1930 as a foreign, minority group. Using a sociological approach to analyse the causality between religion and commerce, further extending the analysis to looking at the social aspect, I argue that it was through religion that a sense of cohesion within the community was fostered, and together with the consolidation of intricate and complex commercial ties, the Nattukottai Chettiar community was able to strengthen their position to negotiate as a minority group in a foreign environment, leading to their socioeconomic success in Lower Delta.